2002
DOI: 10.1002/cncr.10874
|View full text |Cite
|
Sign up to set email alerts
|

The effect of retinoids on premalignant oral lesions

Abstract: BACKGROUND Retinoids have been studied as chemopreventive treatment for patients with oropharyngeal carcinoma. Vitamin A modulates growth and differentiation of cells, and its deficiency enhances susceptibility to carcinogenesis. The chemopreventive mechanism of action of vitamin A is discussed, and a review of clinical results and side effects of the systemic use of vitamin A is included. The objective of the current report was to review the possible role of topical vitamin A and vitamin A derivatives in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 60 publications
2
28
0
2
Order By: Relevance
“…The reported clinical response of previous oral leukoplakia chemoprevention trials ranges from 4% to 67% (25). Vitamin A or retinoid has been the most investigated chemopreventive agent for oral leukoplakia, with a reported response rate of 45% to 67% (26)(27)(28). In the present study, we observed 67.5% clinical response rate (complete or partial) and 20.7% SD after 6 months of intervention.…”
Section: Discussionsupporting
confidence: 57%
“…The reported clinical response of previous oral leukoplakia chemoprevention trials ranges from 4% to 67% (25). Vitamin A or retinoid has been the most investigated chemopreventive agent for oral leukoplakia, with a reported response rate of 45% to 67% (26)(27)(28). In the present study, we observed 67.5% clinical response rate (complete or partial) and 20.7% SD after 6 months of intervention.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, we found a significant reduction in the severity of dysplasia after local treatment with tretinoin in different concentrations (Retinoral®0.005-0.02 %). This is in accordance with other publications that suggest that topical vitamin A may be a possible treatment for mildly dysplastic OLP because of its reported usefulness in inflammatory OLP and its potential impact on mild oral dysplasia [24][25][26]. Further prospective studies are necessary to assess the potential value of retinoids in treating dysplasia.…”
Section: Discussionsupporting
confidence: 90%
“…Topical agents (bleomycin or vitamin A) or systemic oral medications (vitamin A or ␤ -carotene) may be effective in healing OL but do not seem to prevent relapses and malignant change [3,4] . Several studies have shown that the surgical management of OL could reduce the risk of developing carcinoma [5,6] .…”
Section: Introductionmentioning
confidence: 99%